1998
DOI: 10.1002/j.1551-8833.1998.tb08503.x
|View full text |Cite
|
Sign up to set email alerts
|

Legionella in water distribution systems

Abstract: Regular culturing of distribution system samples is the key to successful disinfection. Legionnaires' disease arises from the presence of Legionella in water systems. Legionella can be found within biofilms throughout the entire water distribution system. Control measures such as copper‐silver ionization, superheat‐and‐flush procedures, ultraviolet light, instantaneous heating systems, and hyperchlorination have been applied with variable success. Specific approaches, advantages, disadvantages, and costs of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
1
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 82 publications
1
49
1
6
Order By: Relevance
“…In vitro studies using cocultures have repeatedly demonstrated the intracellular multiplication of L. pneumophila in amoebae (Acanthamoeba, Echinamoeba, Hartmannella, Naegleria, Vahlkampfia, and Dictyostelium) and in a ciliated protozoon (Tetrahymena pyriformis) (12,15,21,39). Amoebae have been observed in water systems associated with Legionnaires' disease (5, 7), and L. pneumophila can recolonize water distributing systems within a few weeks after disinfection (26,27). Batch experiments with tap water showed that L. pneumophila did not multiply in the absence of protozoa, and growth in the presence of a protozoon (Hartmannella) was confirmed by the use of cocultures (14,45).…”
mentioning
confidence: 99%
“…In vitro studies using cocultures have repeatedly demonstrated the intracellular multiplication of L. pneumophila in amoebae (Acanthamoeba, Echinamoeba, Hartmannella, Naegleria, Vahlkampfia, and Dictyostelium) and in a ciliated protozoon (Tetrahymena pyriformis) (12,15,21,39). Amoebae have been observed in water systems associated with Legionnaires' disease (5, 7), and L. pneumophila can recolonize water distributing systems within a few weeks after disinfection (26,27). Batch experiments with tap water showed that L. pneumophila did not multiply in the absence of protozoa, and growth in the presence of a protozoon (Hartmannella) was confirmed by the use of cocultures (14,45).…”
mentioning
confidence: 99%
“…in hospital hot water systems (8). Copper and silver ions are electrolytically generated and introduced into recirculating hot water lines.…”
mentioning
confidence: 99%
“…The first 16 hospitals in the United States that installed these systems remain operational today, and each has reported efficacious results in controlling Legionella in its water distribution system after 5 to 11 years of operation (J. E. Stout, Y. E. Lin, and V. L. Yu, Survey of hospitals using copper-silver ionization for the control of Legionella, abstract from the 5th International Conference on Legionella, p. 80, 2000). The coppersilver ionization systems have outperformed hyperchlorination, superheating and flushing, and UV light systems because of the following advantages: (i) installation and maintenance are easy; (ii) efficacy is not affected by high water temperatures (unlike with chlorine and UV light systems); (iii) residual disinfectant protection occurs throughout the system (unlike with UV light); and (iv) recolonization is delayed because coppersilver ions kill rather than suppress Legionella (unlike with chlorine) (8). Disadvantages of copper-silver ionization systems have rarely been reported.…”
mentioning
confidence: 99%
“…Currently, several methods are available for this purpose, including superheating (thermal eradication), ultraviolet light, copper-silver ionization, hyperchlorination, chloramines, ozone treatment, and chlorine dioxide. 8 Although hot water systems have long been regarded as the primary reservoirs for these organisms, there is growing evidence to suggest that contamination of potable (drinking or cold) water systems may be an even more important risk for nosocomial infections. 9,10 Thus, there is growing interest in evaluating the efficacy and safety of these methods for the treatment of both hot and potable water supplies in hospitals.…”
mentioning
confidence: 99%